Prediction of Masked Hypertension and Masked Uncontrolled Hypertension Using Machine Learning - Hung, Ming-Hui; Shih, Ling-Chieh; Wang, Yu-Ching; Leu, Hsin-Bang; Huang, Po-Hsun; Wu, Tao-Cheng; Lin, Shing-Jong; Pan, Wen-Harn; Chen, Jaw-Wen; Huang, Chin-Chou (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study aimed to develop machine learning-based prediction models to predict masked hypertension and masked uncontrolled hypertension using the clinical characteristics of patients at a single outpatient visit. Methods: Data were derived from two cohorts in Taiwan. The first cohort included 970 hypertensive patients recruited from six medical centers between 2004 and 2005, which were split into a training set (n=679), a validation set (n=146), and a test set (n=145) for model development and internal validation. The second cohort included 416 hypertensive patients recruited from a single medical center between 2012 and 2020, which was used for external validation. We used 33 clinical characteristics as candidate variables to develop models based on logistic regression (LR), random forest (RF), eXtreme Gradient Boosting (XGboost), and artificial neural network (ANN). Results: The four models featured high sensitivity and high negative predictive value (NPV) in internal validation (sensitivity=0.914–1.000; NPV=0.853–1.000) and external validation (sensitivity=0.950–1.000; NPV=0.875–1.000). The RF, XGboost, and ANN models showed much higher area under the receiver operating characteristic curve (AUC) (0.799–0.851 in internal validation, 0.672–0.837 in external validation) than the LR model. Among the models, the RF model, composed of 6 predictor variables, had the best overall performance in both internal and external validation (AUC=0.851 and 0.837; sensitivity =1.000 and 1.000; specificity=0.609 and 0.580; NPV=1.000 and 1.000; accuracy=0.766 and 0.721, respectively). Conclusion: An effective machine learning-based predictive model that requires data from a single clinic visit may help to identify masked hypertension and masked uncontrolled hypertension.